Struktural Fungsional Seni Kerajinan Bambu Masyarakat Selaawi, Garut - Rediansyah, Sandi (Pascasarjana ISBI Bandung, 2019)
Bamboo Craft in Garut, especially in Selawi, plays a significant role for Selawi people. Bamboo is not beneficial for their own benefit but also for their source of income. The famous bamboo craft from Selawi people is a big bird cage. Moreover, a famous event regarding bamboo in Selawi is the simultaneous planting of one billion bamboos of 100 kinds. The existence of Selawi is the manifestation of utilizing natural resources into beneficial products either for the surrounding people or outside society. This research applies sociology approach regarding how Selawi people utilize their surrounding nature. The method applied is qualitative method with functional structuralism to analyze the structure of the society. Bamboo Craft has become the main daily activity of the people. The people are skilful in making bamboos crafts such as bird cage, plaited bamboo, and bamboo musical instrument such as Angklung.Keywords: Bamboo Craft, Selawi People, Functional Structuralism